PERATURAN PRESIDEN NOMOR 33 TAHUN 2020 DALAM PERSPEKTIF PRINSIP OTONOMI DAN DESENTRALISASI - Sesung, Rusdianto; Hadi, Syofyan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe research objective was to determine the existence of Presidential Decree No. 33-2020 in the perspective of the principles of autonomy and decentralization Regional autonomy means regional rights to regulate and manage government affairs decentralized by the central government, including financial management. Regions are given the authority to compile and implement budgets in accordance with regional capacities proportionally and rationally. For that, Presidential Decree No. 33 of 2020 has the potential to conflict with the principles of regional autonomy and decentralization, because it reduces regional independence. The central government should have sufficiently determined guidelines for creating good governance in regional government administration and carried out strict supervision, without specifying detailed and detailed figures.Keywords: decentralization; regional autonomy;regional financeAbstrakTujuan penelitian untuk mengetahui eksistensi Perpres No. 33-2020 dalam perspektif prinsip otonomi dan desentralisasi Otonomi daerah bermakna hak daerah untuk mengatur dan mengurus urusan pemerintahan yang didesentralisasikan oleh pemerintah pusat, termasuk pengelolaan keuangan. Daerah diberikan kewenangan untuk menyusun dan melaksanakan anggaran sesuai dengan kemampuan daerah secara proporsional dan rasional. Untuk itu, Perpres No. 33 Tahun 2020 berpotensi bertentangan dengan prinsip otonomi daerah dan desentralisasi, karena mereduksi kemandirian daerah. Seharusnya, pemerintah pusat cukup menentukan pedoman untuk menciptakan good governance penyelenggaraan pemerintahan daerah dan melakukan pengawasan secara ketat, tanpa menentukan angka yang detail dan rinci.